2015
DOI: 10.1002/anie.201506961
|View full text |Cite
|
Sign up to set email alerts
|

Striking Differences in Properties of Geometric Isomers of [Ir(tpy)(ppy)H]+: Experimental and Computational Studies of their Hydricities, Interaction with CO2, and Photochemistry

Abstract: We prepared two geometric isomers of [Ir(tpy)(ppy)H](+), previously proposed as a key intermediate in the photochemical reduction of CO2 to CO, and characterized their notably different ground- and excited-state interactions with CO2 and their hydricities using experimental and computational methods. Only one isomer, C-trans-[Ir(tpy)(ppy)H](+), reacts with CO2 to generate the formato complex in the ground state, consistent with its calculated hydricity. Under photocatalytic conditions in CH3CN/TEOA, a common r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
44
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 61 publications
(49 citation statements)
references
References 23 publications
4
44
0
1
Order By: Relevance
“…[14][15][16][17] Utilizing clean and renewable solar energy as the power source to accomplish this conversion could be the most economical and environmentally friendly choice. 18 Therefore, the exploration of high-performance photocatalytic systems for CO 2 reduction has been the fundamental goal of experts. In photocatalytic systems, there are three essential steps to achieve the transition from solar energy to chemical energy, [19][20][21][22] including light harvesting, generation of electron-hole pairs, and transferring redox equivalents to reactive centers for redox reactions.…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16][17] Utilizing clean and renewable solar energy as the power source to accomplish this conversion could be the most economical and environmentally friendly choice. 18 Therefore, the exploration of high-performance photocatalytic systems for CO 2 reduction has been the fundamental goal of experts. In photocatalytic systems, there are three essential steps to achieve the transition from solar energy to chemical energy, [19][20][21][22] including light harvesting, generation of electron-hole pairs, and transferring redox equivalents to reactive centers for redox reactions.…”
Section: Introductionmentioning
confidence: 99%
“…The proposed reaction mechanism of [Ir(tpy)(ppy)Cl] + includes the formation of a one‐electron‐reduced (OER) species, followed by the loss of the coordinated Cl − and formation of the hydride species([Ir(tpy)(ppy)H] + ) with further reduction. However, when CO 2 reduction reaction was conducted over isolated [Ir(tpy)(ppy)H] + , the [Ir(tpy)(ppy)H] + was not the active catalyst, instead the hydride complex acted as a photo acid to produce a penta‐coordinated Ir complex acting as the true active catalyst for CO 2 reduction to CO . Recently, several research groups have reported new mononuclear Ir complex photocatalysts for CO 2 reduction .…”
Section: Introductionmentioning
confidence: 99%
“…Mechanistic studies were performed and suggested the formation of an [Ir(tpy)(ppy)H] + intermediate, as the virtual photocatalytically active species; moreover, the formation of dinuclear complexes was discussed as one potential deactivation pathway (Figure ). The catalytic cycle, with a focus on the reaction of the [Ir(tpy)(ppy)H] + intermediate with CO 2 , was investigated in more detail by using spectroscopic and computational methods . The two possible geometrical isomers, i. e ., the C ‐ trans and the C ‐ cis hydride isomer, yielded the same penta‐coordinate two‐electron reduced [Ir(tpy)(ppy)] 0 complex within the photocatalytic cycle to which CO 2 was subsequently bound in a C ‐ trans ‐fashion.…”
Section: Terpyridine Complexes As Catalysts In Energy Conversion Appmentioning
confidence: 99%